In search of an epistemology for administrative research in Latin America - Hidalgo Sánchez, Augusto (2019)
The Administration is a science that contains theories, principles, technologies and practices. As a field of research, it has two major problems. First, it has been impelled both by universities and by organizations promoting the development of science to the use of positivist or quantitative epistemology, as if it were a natural science. Second is to study the applicability to everything discovered and created in developed countries to the reality of Latin America, especially because the social reality of this subcontinent has its own peculiarities. Social Anthropology can help a lot in these efforts, with the use of its essentially qualitative research methods.